Profiling the heterogeneity of colorectal cancer consensus molecular subtypes using spatial transcriptomics - Valdeolivas, Alberto; Amberger, Bettina Theresia; Giroud, Nicolas; Richardson, Marion; Gálvez, Eric J. C.; Badillo, Solveig; Julien-Laferrière, Alice; Túrós, Demeter; Voith von Voithenberg, Lena; Wells, Isabelle; Pesti, Benedek; Lo, Amy A.; et al. (npj precision oncology, 2024)
The consensus molecular subtypes (CMS) of colorectal cancer (CRC) is the most widely-used gene expression-based classification and has contributed to a better understanding of disease heterogeneity and prognosis. Nevertheless, CMS intratumoral heterogeneity restricts its clinical application, stressing the necessity of further characterizing the composition and architecture of CRC. Here, we used Spatial Transcriptomics (ST) in combination with single-cell RNA sequencing (scRNA-seq) to decipher the spatially resolved cellular and molecular composition of CRC. In addition to mapping the intratumoral heterogeneity of CMS and their microenvironment, we identified cell communication events in the tumor-stroma interface of CMS2 carcinomas. This includes tumor growth-inhibiting as well as -activating signals, such as the potential regulation of the ETV4 transcriptional activity by DCN or the PLAU-PLAUR ligand-receptor interaction. Our study illustrates the potential of ST to resolve CRC molecular heterogeneity and thereby help advance personalized therapy.